Association of non‐invasive electrocardiographic risk factors with left ventricular systolic function in post‐myocardial infarction patients with mildly reduced or preserved ejection fraction: Insights from the PRESERVE‐EF study. Issue 5 (6th July 2022) - Tsimos, Konstantinos P.; Korantzopoulos, Panagiotis; Arsenos, Petros; Doundoulakis, Ioannis; Tsiachris, Dimitrios; Antoniou, Christos‐Konstantinos; Krikonis, Konstantinos; Sideris, Skevos; Dilaveris, Polychronis; Triantafyllou, Konstantinos; Soulaidopoulos, Stergios; Kanoupakis, Emmanuel; et al.
Abstract: Background: Electrocardiographic non‐invasive risk factors (NIRFs) have an important role in the arrhythmic risk stratification of post‐myocardial infarction (post‐MI) patients with preserved or mildly reduced left ventricular ejection fraction (LVEF). However, their specific relation to left ventricular systolic function remains unclear. We aimed to evaluate the association between NIRFs and LVEF in the patients included in the PRESERVE‐EF trial. Methods: We studied 575 post‐MI ischemia‐free patients with LVEF≥40% (mean age: 57.0 ± 10.4 years, 86.2% men). The following NIRFs were evaluated: premature ventricular complexes, non‐sustained ventricular tachycardia (NSVT), late potentials (LPs), prolonged QTc, increased T‐wave alternans, reduced heart rate variability, and abnormal deceleration capacity with abnormal turbulence. Results: There was a statistically significant relationship between LPs (Chi‐squared = 4.975; p  < .05), nsVT (Chi‐squared = 5.749, p  < .05), PVCs ( r = −.136; p  < .01), and the LVEF. The multivariate linear regression analysis showed that LPs ( p  = .001) and NSVT ( p  < .001) were significant predictors of the LVEF. The results of the multivariate logistic regression analysis indicated that LPs (OR: 1.76; 95% CI: 1.02–3.05; p  = .004) and NSVT (OR: 2.44; 95% CI: 1.18–5.04; p  = .001) were independent predictors of the mildly reduced LVEF: 40%–49% versus the preserved LVEF: ≥50%. Conclusion: Late potentials and NSVT are independently related to reduced LVEF while they are independent predictors of mildly reduced LVEF versus the preserved LVEF. These findings may have important implications for the arrhythmic risk stratification of post‐MI patients with mildly reduced or preserved LVEF.